Risk factors for delayed gastric emptying after pancreatoduodenectomy: a 10-year retrospective study - Carlos Jiménez-Romero; Agustín de Juan Lerma; Alberto Marcacuzco Quinto; Oscar Caso Maestro; Laura Alonso Murillo; Paula Rioja Conde; Iago Justo Alonso (Annals of Medicine)
Background Delayed gastric emptying (DGE) is a frequent complication of pancreatoduodenectomy (PD) and is associated with prolonged hospital stay, readmission, increased hospital costs and decreased quality of life. However, the pathophysiology of DGE remains unclear.Methods This is a retrospective study of patients who underwent PD for pancreatic or periampullary tumours. All these patients were operated between January 2012 and February 2023. The patients were divided into four groups according to the development of DGE after PD: No DGE, DGE grade A, DGE grade B and DGE grade C. The groups were compared in terms of outcomes and complications. We also analysed the preoperative and perioperative risk factors for DGE development.Results Between January 2012 and February 2023, a total of 250 patients underwent PD. These patients were divided into four groups: No DGE (n = 152); DGE grade A (n = 42); DGE grade B (n = 45); and DGE grade C (n = 11). The incidence of the postoperative pancreatic fistulas (POPFs) grade B/C was significantly higher in the DGE grade C group (p < .001), and the rates of post-pancreatectomy haemorrhage (p = .004) and reoperation (p < .001) were significantly higher in the DGE grade B/C groups. A significantly higher rate of grade III–IV Clavien–Dindo complications (p < .001), longer intensive care unit (p < .001) and longer hospital stays (p < .001) were observed in the DGE grade C group; and 90-day mortality (p < .001) and morbidity (p < .001) were significantly higher in the DGE grade B/C groups. Multivariate analysis demonstrated that the POPF grade B/C was a risk factor of DGE grade B/C (OR: 9.147; 95%CI: 4.125–20.281; p < .001).Conclusions POPF B/C is a risk factor for grade B/C DGE. Prevention of surgical complications and early treatment could contribute to the decreased incidence of DGE.